2009
DOI: 10.1111/j.1439-0272.1997.tb00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging effect of N-acetyl-L-cysteine against reactive oxygen species in human semen: a possible therapeutic modality for male factor infertility?

Abstract: A new approach to reduce the level of reactive oxygen species (ROS) in human semen by using N-acetyl-L-cysteine (NAC) was evaluated. Semen samples were incubated with or without NAC (1.0 mgml-') at room temperature. The chemiluminescent signal of the oxidation of lumi-no1 was detected by means of an MTP reader after 0, 20, 40, 60 and 120 min, respectively, using 200 pM luminol. In addition, the dose-dependent action of NAC (0.1, 1.0 and 5.0 mg ml-') and the influence of NAC on functional sperm parameters (moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 35 publications
2
61
0
1
Order By: Relevance
“…Some studies have shown that antioxidants (e.g., vitamin E, glutathione, N-acetyl cysteine, catalase and ferulic acid) are effective in reducing ROS levels and in preventing the decline in sperm motility during sperm processing. [93][94][95][96] In contrast, other studies have reported that antioxidants (e.g., glutathione and catalase) are ineffective in protecting spermatozoa from the loss of motility during sperm processing. [97][98][99] It is important to note that sperm samples from infertile men may be more susceptible to oxidative injury (from semen processing) and be afforded greater protection by antioxidants than samples from fertile men.…”
Section: Role Of In Vitro Antioxidants In Protecting Spermatozoa Frommentioning
confidence: 74%
“…Some studies have shown that antioxidants (e.g., vitamin E, glutathione, N-acetyl cysteine, catalase and ferulic acid) are effective in reducing ROS levels and in preventing the decline in sperm motility during sperm processing. [93][94][95][96] In contrast, other studies have reported that antioxidants (e.g., glutathione and catalase) are ineffective in protecting spermatozoa from the loss of motility during sperm processing. [97][98][99] It is important to note that sperm samples from infertile men may be more susceptible to oxidative injury (from semen processing) and be afforded greater protection by antioxidants than samples from fertile men.…”
Section: Role Of In Vitro Antioxidants In Protecting Spermatozoa Frommentioning
confidence: 74%
“…The most noteworthy studies are those performed by Baker et al, 54 Oeda et al 58 and Lopes et al, 5 which showed positive effects with varying doses in vitro. Baker et al 54 observed reduced ROS production and improved motility with doses ranging from 1 to 10 mmol l 21 , whereas Oeda et al 58 observed preserved motility with doses from 0.1 to 15 mg ml 21 and Lopes et al 5 found reduced DNA damage with 0.1 mmol l 21 of NAC.…”
Section: Antioxidant Studies Effectmentioning
confidence: 96%
“…To assess whether PB-and metyrapone-stimulated ROS increase plays an important role in CYP induction, we decided to modulate the cellular ROS production by either overexpression of uncoupling protein 1 (UCP-1) (27) or ROS scavenging by N-acetyl L-cysteine (NAC) (28). Transfection of UCP-1 in LMH cells provoked a considerable decrease of the effect of PB and metyrapone on mRNA levels of both CYP2H1 and CYP3A37 (Fig.…”
Section: Pb and Metyrapone Affect Mitochondrial Membrane Potential Rosmentioning
confidence: 99%